Maximization of soybean exploration. IV. effect of stem cutting height on the production of hay and grains from regrowth - Rezende, Pedro Milanez de; Favoretto, Carlos Roberto Simon (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to verify the effect of height of the cut on production of hay and grains from regrowth of soybean. The experiment was conducted in the “Escola Superior de Agricultura de Lavras", Lavras, MG in a Dusky-Red Latosol dystrophic soil, in the agricultural year of 1981/82. The experimental design was a randomized complete block design with five treatments (cuttings with 20 cm, 25 cm, 30 cm and 35 cm and no cutting) and four replications. The higher yield of fresh matter, hay and dry matter were obtained with the lower height of cuttings (20 cm and 25 cm). There was no significant difference between the yield of grains of the regrowth from the cuttings with 30 cm an 35 cm of height compared with no cutting. The same was verified with insertion height of the first pod. The yield of straw and total mass (straw + grains), the plant height and lodging were always higher in the treatment with no cutting.